Analisis Penerapan Metode Economic Order Quantity (EOQ) dan Penentuan Harga Jual Pada CV. Prima Abadi Jaya - Sigarlaki, Lauren; Setyawati, Vincentia Devina (SUSTAINABLE JURNAL AKUNTANSI, 2023)
Printing on CV. Prima Abadi Jaya is a company engaged in the printing industry. This study aims to determine the optimal amount of raw material inventory at CV. Prima Abadi Jaya using the Economic Order Quantity (EOQ) method from January to December 2021. Data collection is carried out to calculate the optimal quantity and determine the selling price applied by the company using the full costing method. Calculation of Total Inventory Cost (TIC) if the company applies the Economic Order Quantity (EOQ) method for magazine products, the Total Inventory Cost (TIC) of raw materials is Rp. 675,005 and for book products, the Total Inventory Cost (TIC) of raw materials is Rp. 591,423. calculation of the cost of goods manufactured and the optimal selling price on the CV. Prima Abadi Jaya for magazine products is Rp. 25,268, for book products is Rp. 11,768.